2005
DOI: 10.1176/jnp.17.4.533
|View full text |Cite
|
Sign up to set email alerts
|

The Clock Drawing Test: Diagnostic, Functional, and Neuroimaging Correlates in Older Medically Ill Adults

Abstract: This study evaluated the clock drawing test (CDT), a screening test sensitive to executive function, in 70 elderly psychiatric consultation patients. The CDT was compared to the Mini-Mental Status Examination (MMSE) on associations with psychiatric diagnoses, disposition status and radiographic findings. CDT and MMSE were correlated, and scores differed across psychiatric subgroups. In multivariate analysis, only age and CDT predicted disposition status. A lower CDT score correlated with a higher intercaudate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 31 publications
1
30
0
3
Order By: Relevance
“…In addition, Samton et al (2005) found that MMSE performance and CDT were correlated as anticipated, but CDT was a more sensitive and consistent predictor of disposition compared to the MMSE. Therefore, early screening of cognitive decline to prevent and apply efficient and timely treatments in elderly is very important.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, Samton et al (2005) found that MMSE performance and CDT were correlated as anticipated, but CDT was a more sensitive and consistent predictor of disposition compared to the MMSE. Therefore, early screening of cognitive decline to prevent and apply efficient and timely treatments in elderly is very important.…”
Section: Discussionsupporting
confidence: 56%
“…CDT is a screening test sensitive to executive function. One study showed that CDT was superior to MMSE for predicting degree of executive function and functional status in an elderly medically ill population [28]. Story-retelling tasks are also useful to diagnose AD, because episodic memory deficits are the hallmark of AD.…”
Section: Discussionmentioning
confidence: 99%
“…CDT is a multifaceted and a multidimensional measure test which is thought to test the visuoconstructive and the visuospatial skills, the symbolic and the graphomotor representation, the auditory language skills, the hemiattention, the semantic memory, the conceptual abilities, and the executive function, which includes organization, planning, and parallel processing [7,8].…”
Section: Introductionmentioning
confidence: 99%